A new large didelphid of the genus Thylophorops (Mammalia: Didelphimorphia: Didelphidae), from the late Tertiary of the Pampean Region (Argentina) - Goin, Francisco J.; Zimicz, Natalia; de Los Reyes, Martín; Soibelzon, Leopoldo (Zootaxa, 2009)
We describe Thylophorops lorenzinii sp. nov. (Marsupialia, Didelphidae), the largest known didelphid opossum, living or extinct. Its type specimen comes from Late Pliocene levels at Punta San Andrés, southeastern Buenos Aires Province, Argentina. With an estimated body mass between 4.8 and 7.4 kg, it obviously surpasses that of the (up to now) largest didelphid, the living Didelphis virginiana Kerr. In addition to its larger size, the new species differs from T. chapalmalensis Ameghino and T. perplanus Ameghino in that its lower molars have more labially salient hypoconids and proportionally large hypoconulids which are not antero-posteriorly compressed.